Voltage‐operated Ca2+ currents and Ca2+‐activated Cl– currents in single interstitial cells of the guinea‐pig prostate. (September 2014) - Lang, Richard J.; Tonta, Mary A.; Takano, Hiromichi; Hashitani, Hikaru
<x xml:space="preserve">Abstract</x> Objective To investigate the expression of 'T‐type' and 'L‐type' voltage‐operated Ca2+ channels in single interstitial cells of the guinea‐pig prostate. Material and Methods Whole‐cell and perforated patch‐clamp techniques were applied to prostatic interstitial cells (PICs) dispersed using collagenase. Results In contrast to prostatic myocytes, PICs under voltage clamp and filled with K+ (130 mm) were distinguished by the absence of a voltage‐operated transient outward K+ current or spike discharge upon membrane depolarisation when under current clamp. Depolarisation of Cs+‐filled PICs evoked an inward current at potentials positive to −60 mV, which peaked in amplitude near 0 mV. This inward current increased when Ba2+ (5 mm) replaced the external Ca2+ (1.5 mm) and displayed a variable sensitivity to the inhibitory actions of conditioning depolarisations to −40 mV applied before the test depolarisation or to 1 μm nifedipine, the 'L‐type' Ca2+ channel blocker. A residual inward current recorded in nifedipine was blocked by 10 μm Ni2+. Cs+‐filled PICs also displayed a slowly inactivating outward current that was little affected by nifedipine, reduced by the Cl– channel blocker, niflumic acid (10 μm) and blocked by Ba2+ or a conditioning depolarisation. Conclusion PICs express both a small 'T‐type' Ca2+ channel current (ICa) and a large 'L‐type' ICa. Ca2+ influx through 'T‐type' ICa was an essential trigger for the activation of a Ca2+‐activated Cl–‐selective current. The dependence of PIC Ca2+ signalling on 'T‐type' and 'L‐type' ICa is unique compared with other interstitial cells of the urogenital tract and may well be pharmaceutically exploitable.